Towards a practical usage for the Sleuth Kit supporting file system add-ons - Shin, Yeonghun; Shon, Taeshik (Forensic Science International: Digital Investigation, 2024)
Most modern digital devices with storage utilize a file system to manage files and directories. Consequently, when digital forensic investigators derive evidence from such devices, they collect and analyze data stored on them through file system analysis. However, there are numerous types of file systems, with new ones continually being developed. Each file system possesses a distinct metadata structure and file management system. Therefore, investigators must possess prior knowledge of the specific file system being examined. Nevertheless, it is challenging for practitioners to be knowledgeable about all existing file systems. To address this issue, forensic software such as The Sleuth Kit (TSK), an open-source forensic tool, is employed for investigations. However, even these tools may not offer complete support for relatively recent file systems. Hence, we propose a structure for integrating a new file system into the open-source forensic tool TSK. Additionally, to validate this proposed structure, we demonstrate that support for five file systems (Ext4, XFS, Btrfs, F2FS, and Hikvision) can be added following this framework. To achieve this, we conducted an analysis of the metadata and file management scheme for these five file systems. Furthermore, we examined the operational procedures of the TSK framework. Based on these analyses, investigation capabilities for the five file systems have been incorporated into TSK. Moreover, reliability verification experiments were conducted on the developed tools; and performance evaluation was carried out in comparison with other commercial digital forensic tools. The findings of this study can serve as a foundation for future forensic studies based on file systems. Additionally, the TSK developed based on the proposed structure can assist investigators in conducting digital forensics effectively.
Keywords: Btrfs; File management; Filesystem; Forensic tools; Forensics investigators; Management systems; Open-source; Structure management; The sleuth kit; XFS; Btrfs; Digital forensics; F2FS; Filesystem; The sleuth kit; XFS